Anal fissure: Diagnostic and therapeutic considerations with special reference to internal lateral sphincterotomy - Berrudez Villegas, Jorge; Kamaid, Emil (Cirugía del Uruguay, 1982)
The authors analyzed a series of 80 cases and revised bibliography concluding that i t is essential to astablish the diagnosis of idiopathic anal fissure, discarding associated pathologv, in particular posterior abcesses. As elective treatment they favour. subcutaneous internal lateral sphyncterotomy by reason of its higher perccntagc of cures with fewer complications and sequella. In the series considered there was a single recurrencv (1.25%) which resulted from diagnostical error, with no sequellae, consequently the authors recommcnd this procedure specifying indications and contraindications.